Transcriptome Profiling Provides Insights Into Potential Antagonistic Mechanisms Involved in Chaetomium globosum Against Bipolaris sorokiniana - Darshan, K.; Aggarwal, Rashmi; Bashyal, Bishnu Maya; Singh, Jagmohan; Shanmugam, V.; Gurjar, Malkhan S.; Solanke, Amolkumar U. (Frontiers in Microbiology, 2020)
Chaetomium globosum Kunze is recognized as a potential biocontrol fungus against spot blotch of wheat caused by Bipolaris sorokiniana. It’s molecular mechanism of biocontrol activity and biosynthetic pathways involved are not yet elucidated. Here global transcriptome profiling of C. globosum strain Cg2 during interaction with B. sorokiniana isolate BS112 using RNA-seq was performed in order to gain insights into the potential mechanisms of antagonism. The Illumina HiSeq platform (2×150 bp) yielded an average of 20-22 million reads with 50-58% GC. De novo assembly generated 45582 transcripts with 27957 unigenes. Transcriptome analysis displayed distinct expression profile in the interaction (Cg2-BS112), out of which 6109 unique DEGs were expressed. The predominant transcripts classified as genes involved in “catalytic activity” constituted 45.06%, of which, 10.02% were associated with “hydrolytic activity” (GO:0008152) and similarly in the biological process, 29.18% of transcripts were involved in “metabolic activity” (GO:0004096; GO:0006979). Heat map and cluster categorization suggested an increase in the expression levels of genes encoding secondary metabolites like polyketide synthase (GO:0009058), S-hydroxymethyl glutathione dehydrogenase (GO:0006069), terpene cyclase (EC 4.2.3.-), aminotran_1_2 domain-containing protein (GO:0009058) and other hydrolytic CAZYmes such as glycosyl hydrolase (GH) family (GH 13, GH 2, GH 31 and GH 81; GO:0005975), cellulase domain-containing protein, chitinases, β-1, 3-glucanases (GO:0004565), glucan endo-1,3-beta-glucanase (GO:0052861), and proteases (GO:0004177). The obtained RNA-seq data was validated by RT-qPCR using 20 randomly chosen genes, showing consistently with the RNA-seq results. The present work is worldwide the first effort to unravel the biocontrol mechanism of C. globosum against B. sorokiniana. It generated a novel dataset for further studies and facilitate the improvement of the gene annotation models in the C. globosum draft genome.